Quantitative Characterization of Pore Arrangement in Pore Bands in Pressure Die Cast AZ91 Magnesium Alloy by Image Processing - Leo Prakash (Materials Science Forum, 2006)
Microporosity is the major processing defect in pressure die cast AZ91 magnesium alloy. There is a big difference in the arrangement of pores in different regions of the castings. The present work explains the pore arrangement in pore bands and other regions. Quantification and characterization of pores in pore bands is expected to be useful to understand the process-propertymicrostructure correlation. A computational microstructural (image) analyzing technique has been developed by a programming language to quantify and analyze the micropores in pore bands. The pore band regions and the rest were separated and quantified. In addition, image analyzing technique was used to measure the clustering tendency of porosity in pore bands and it was compared with other regions.